2014
DOI: 10.1111/pbi.12248
|View full text |Cite
|
Sign up to set email alerts
|

Compositional differences between near‐isogenic GM and conventional maize hybrids are associated with backcrossing practices in conventional breeding

Abstract: SummaryHere, we show that differences between genetically modified (GM) and non-GM comparators cannot be attributed unequivocally to the GM trait, but arise because of minor genomic differences in near-isogenic lines. Specifically, this study contrasted the effect of three GM traits (drought tolerance, MON 87460; herbicide resistance, NK603; insect protection, MON 89034) on maize grain composition relative to the effects of residual genetic variation from backcrossing. Important features of the study included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
2
25
1
1
Order By: Relevance
“…The observed variability in grain composition can be attributed to these differences. It is well documented that both growing environment and germplasm have a strong influence on the composition of maize (Harrigan et al ., ; Reynolds et al ., ; Skogerson et al ., ; Venkatesh et al ., ). These results are consistent with the expectation that these events have little effect on composition, whether as single events or stacked with one another, and are a good representation of the variability in composition inherent in maize.…”
Section: Resultsmentioning
confidence: 97%
“…The observed variability in grain composition can be attributed to these differences. It is well documented that both growing environment and germplasm have a strong influence on the composition of maize (Harrigan et al ., ; Reynolds et al ., ; Skogerson et al ., ; Venkatesh et al ., ). These results are consistent with the expectation that these events have little effect on composition, whether as single events or stacked with one another, and are a good representation of the variability in composition inherent in maize.…”
Section: Resultsmentioning
confidence: 97%
“…This study showed that genetic changes accumulated spontaneously across many conventional germplasm (i.e., standing variation). Another recent study of many maize varieties (both conventional and GM) showed that most of the observed compositional differences were associated with the backcrossing practices from conventional breeding (Venkatesh et al, 2015). Repetitive DNA sequences and structural variations in plants have the potential to contribute to genetic change.…”
Section: Conventional Plant Breeding Sources Of Genetic Variation Usementioning
confidence: 99%
“…As a result, extensive regulatory requirements for GM crops, which use a comparative safety assessment process, are now in place (König et al, 2004;Cellini et al, 2004;EFSA, 2006;Paoletti et al, 2008;CODEX, 2009;Privalle et al, 2012;Hoekenga et al, 2013;Prado et al, 2014). Since that time, numerous studies have found that GM varieties are compositionally equivalent to conventional crops Herman and Price, 2013;Hoekenga et al, 2013;Ricroch, 2013;Xu et al, 2014;Ladics et al, 2015aLadics et al, , 2015bCurran et al, 2015;Venkatesh et al, 2015Venkatesh et al, , 2016. The exceptions are a few cases where the desired trait confers an intended change in composition, such as improved nutrition (Chassy et al, 2008).…”
Section: Plant Selection Practices Minimize Unsafe Unintended Changesmentioning
confidence: 99%
“…This result suggests that parental lines could have presented residual heterozygosis for these loci due to multiple conventional breeding steps rather than to the transgene introduction (Harrigan et al, 2010;Venkatesh et al, 2014). Moreover, the Bt-RR version (DK747MGRR) exhibited the lowest genetic diversity value despite the fact that both, the MON810 event and the NK603 event, were independently inserted in the maize genome and stacked by backcrossing (CERA, 2012).…”
Section: Discussionmentioning
confidence: 99%